Optimalisasi Layanan INSILITE (Integrated Library System) di Perpustakaan Pelita Ilmu Desa Buding Kabupaten Belitung Timur - Kiftiyah, Maryatul; Maulana, Chika Aulya; Asrori, Bahrul; Kusuma, Rafles Abdi (AL QUWWAH : Jurnal Pengabdian Masyarakat, 2025)
The progress of a nation is largely determined by the extent to which its people have the awareness to increase their knowledge. Increasing community knowledge, apart from being determined by formal education, will also be greatly helped if the community has a good literacy culture through the use of libraries. The existence of a village library will really help improve literacy culture, such as the one at the Pelita Ilmu Library in Buding Village, Kelapa Kampit District, East Belitung Regency. However, in implementing Pelita Ilmu library services, the management is still not optimal in providing INSILITE (Integrated Library System) based services. Therefore, through Community Service Activities, activities are carried out in the form of Optimizing the Village Library by arranging the book collection, improving the layout, improving the library system and socializing the use of the village library to the community. This activity resulted in the Pelita Ilmu library service in Buding Village becoming increasingly optimal and becoming a pleasant and easily accessible place for the community. So that people can get the information and knowledge they need, including preserving the village's cultural heritage.